2021
DOI: 10.1007/s11701-021-01227-2
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of robotic-assisted vs conventional laparoscopic surgery among patients undergoing resection for rectal cancer: an observational single hospital study of 300 cases

Abstract: Robotic-assisted laparoscopic surgery attempts to facilitate rectal surgery in the narrow space of the pelvis. The aim of this study is to compare the outcomes of robotic versus laparoscopic surgery for rectal cancer. Monocentric retrospective study including 300 patients who underwent robotic (n = 178) or laparoscopic (n = 122) resection between Jan 2009 and Dec 2017 for high, mid and low rectal cancer. The robotic and laparoscopic groups were comparable with regard to pretreatment characteristics, except for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…However, longer operating times in robotic surgery due to set up, docking, and increased costs has limited its widespread adoption. 7 Moreover, additional training is required for staff to operate the machinery, and there is a learning curve for surgeons learning this new platform. However, recent studies have demonstrated significant reductions in length of stay, conversion to open surgery rate, and hospital costs for surgeons performing a high volume of robotic surgery.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, longer operating times in robotic surgery due to set up, docking, and increased costs has limited its widespread adoption. 7 Moreover, additional training is required for staff to operate the machinery, and there is a learning curve for surgeons learning this new platform. However, recent studies have demonstrated significant reductions in length of stay, conversion to open surgery rate, and hospital costs for surgeons performing a high volume of robotic surgery.…”
Section: Discussionmentioning
confidence: 99%
“…5 Robotic surgery has been developed to offer advantages over laparoscopic techniques, particularly in anatomically limited spaces such as a narrow pelvis. [6][7][8] It provides better three-dimensional depth of field, seven degrees of wrist-like motion allowing increased and more natural range of motion, tremor-filtering articulating instruments, a stable camera platform, results in better ergonomics and less surgeon fatigue. 7 Furthermore, the robotic approach is useful in allowing more precise optical definition and dissection in arduous pelvic dissection, especially in complicated diverticulitis.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In accordance with the results above, the three mean distances were 72.96 ± 9.75 mm, 41.60 ± 6.73 mm, and 99.58 ± 13.07 mm, respectively. Although the SMA root, aorta abdominalis branch, and the level of sacral promontory can be used as location markers for IMA roots, the SMA root and aorta abdominalis branch are located behind the peritoneum, requiring a deeper dissociative Toldt space [25]. The level of the sacral promontory serves as a marker of the entrance to the pelvis and is more easily determined.…”
Section: Discussionmentioning
confidence: 99%